The Unbearable Lightness of Being Nothing: Einmal ist Keinmal in Otto And Nietzsche - Kandler, Renate Anna (Université d'Ottawa | University of Ottawa, 2011)
Using void as a starting point this article provides an Ottonian and Nietzschian reading of ‘nothingness.’ Nietzsche’s Dionysian Worldview describes the path laid out by “saint and tragic artist” while Otto’s Das Heilege provides the parallel path of mystic and artist. Both cases lead to a discourse on emptiness and no-thingness. These categorical types (mystic/saint and artist) are localized through mystic St. Faustina Kowalska and minimalist sculptor Fred Sandback. Where Faustina interiorizes an abyss of nothingness, Sandback exteriorizes nothingness in his artwork. Her hidden, spiritualized void is paralleled in his exposed aesthetic display. An analysis of each reveals the ways in which Nietzsche and Otto engage with nothingness, respectively affirming and denying the sentiment that einmal ist keinmal (once is not enough).